Alberta School Principals’ Use of Professional Portfolios in Teacher Hiring - Kelly, Darron; Hancock, Stephanie (Canadian Journal of Education/Revue canadienne de l’éducation, 2018)
<span style="line-height: 107%; font-family: 'Times New Roman',serif; font-size: 12pt; mso-fareast-font-family: 'Times New Roman'; mso-fareast-theme-font: minor-fareast; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">Creating a professional portfolio is a requirement for most pre-service teachers in Alberta. Little is known, however, about principals’ use of applicant portfolios in hiring. In response, researchers conducted an online survey of principals throughout the province. Findings indicate a preference for traditional job application items (e.g., a resumé, reference letters, and letter of introduction) and teacher competence indicators (e.g., teacher mentor and school administrator assessments, student assessment methods, and a classroom management plan). Examining attitudes and hiring practices provides direction for creating portfolios that attend to the actual needs and interests of principals in the province, thereby enhancing the employment prospects of new teachers.